ECONOMIC ANALYSIS OF THE IMPACT OF DIFFEREN LEVEL OF SOIL SALINITY ON THE PRODUCTIVITY OF WHEAT CROP IN WASIT PROVINCE - & Farhan, Nassir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The study sample included 590 farmers in Wasit province, has been taking samples of soils that the first two levels of the samples  0-15 cm, and second 15-30 cm, from different agricultural people in the province, was the level of salinity of the soil analysis, in the laboratories of the Faculty of agricultural techniques / Musayyib, SPSS software to analyze the function and use the influence of the level of soil salinity on the productivity of wheat crop, and traversed by testing the function of class I and II, and turned out to be an inverse relationship which determine the level of critical soil salinity b 12.13 Desiminz / m, a level which even then the average revenue dunum  with average costs, also identified the level of salinity of the soil, which then become the productivity of the crop is equal to zero when the function 18.163 ds m-1. The study recommended that the Department of Agriculture is committed to non-introduction of land that soil salinity level higher than 12 ds m-1 within the agricultural plan for the province of Wasit, because that is a waste of economic resources. The study also recommended the need to draw a map of the levels of land salinity in general to determine the crop structure that is appropriate different levels of salinity, and recommended the encouragement of farmers who are their lands with high levels of soil salinity on other crops more tolerant to salinity, such as barley, alfalfa and clover, and others.